From revolutionary dragon, to timid, and now rejuvenated: The stages of Chinese foreign policy - Vélez Serrano, Mayra (2018)
Since Xi Jinping's takeover, there has been debate about the future of China's foreign policy. However, these debates lack historical or ideological context. Given the hyper-centralized nature of the Chinese political system, foreign policy must be analyzed using the Guiding Ideologies and Guiding Principles created by different leaders of the country as a foundation. This allows us to understand both the ideological factors of its foreign policy, as well as the strategies and actions that China has taken internationally. Through the analysis of primary documents, speeches, white papers and secondary documents, this research proposes that China's foreign policy (since 1949) has had three distinct stages. The first stage, which extends during the period in which Mao Zedong was in power, is characterized by the creation of Guiding Principles of foreign policy that focused on international revolutionary activism. The second stage, which begins with Deng Xiaoping and concludes with Hu Jintao (1978-2012), is defined as a timid stage, reluctant to draw attention or take leadership internationally. While the last stage, has begun with Xi Jinping (2013) and is differentiated by greater assertiveness, confidence and willingness to take leadership before the international system. This article is a brief summary of the historical and ideological factors that put in context the evolution of China's foreign policy and the relationship of Xi Jinping with the policy of its predecessors.